Multi-Instrument Assessment of Phytoplankton Abundance and Cell Sizes in Mono-Specific Laboratory Cultures and Whole Plankton Community Composition in the North Atlantic - Menden-Deuer, Susanne; Morison, Françoise; Montalbano, Amanda L.; Franzè, Gayantonia; Strock, Jacob; Rubin, Ewelina; McNair, Heather; Mouw, Colleen; Marrec, Pierre (Frontiers in Marine Science, 2020)
The abundance and size distribution of plankton in the surface ocean are key metrics to understanding primary and export production, food web dynamics, and the optical properties of the water column. Here we quantified cell size and abundance of phytoplankton species from mono-specific laboratory cultures, using optical, electrical, and image-based benchtop instrumentation. Moreover, we combined particle size distribution and size fractionated chlorophyll a (Chl a) analysis with image analysis to estimate phytoplankton community composition and abundance comparing a high and low biomass station in the North Atlantic during springtime. In laboratory cultures, we found generally good agreement in estimates of both particle concentration and particle size among instruments. Image-based approaches (e.g. microscopy, FlowCam) delivered somewhat lower cell abundance estimates, because image-based instruments distinguish cells from non-living objects. Image-based approaches also measured 10-20% greater cell sizes, because measurements were based only on in-focus images of the target species. Particle counters delivered indistinguishable estimates of size and abundance with much lower effort and technical expertise required. Maximum coefficient of variation for cell abundance and size did not exceed 10 and 15% respectively. Measurement precision was consistent across instrument type and across the size spectrum from 3 to >40 µm equivalent spherical diameter. For whole plankton community analysis from the North Atlantic, combined estimation of Chl a concentration and image-based diversity assessments resolved the dominant contributing phytoplankton species and spatial differences in the size structure of the plankton community. These results provide strong support for using particle counters, that can rapidly process large volumes of samples, to quantify particle size and abundance, including rarer, larger particles. Species identities and community composition can be revealed by supplemental, image-based approaches. Application of this coupled approach can help identify fundamental ecosystem characteristics such as particle size spectra that affect primary production, trophic transfer and export. Ultimately, the tremendous species diversity of plankton can be leveraged as particle tracking and identification keys, such as near-real time identification of coherent water masses.